2002
DOI: 10.1590/s0041-87812002000300001
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum levels of ca 72-4, cea, ca 19-9, and Alpha-fetoprotein in patients with gastric cancer

Abstract: INTRODUCTION: The clinical importance of preoperative serum levels of CA 72-4, carcinoembryonic antigen (CEA), CA 19-9, and alpha-fetoprotein (AFP) was prospectively evaluated in 44 patients with gastric cancer. METHOD: The serum tumor marker levels were determined by commercial radioimmunoassay kits. Positivity for CA 72-4 (>4 U/mL), CEA (>5 ng/mL), CA 19-9 (>37 U/mL), and AFP (>10 ng/mL) were correlated according to the stage, histology, and lymph node metastasis. RESULTS AND DISCUSSION: CA 72-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 16 publications
(21 reference statements)
2
32
0
2
Order By: Relevance
“…To conclude, we found that AMAS testing discrimination of neoplasia was significantly different from random, with sensitivities and specificities similar to other clinical tests such as prostate-specific antigen (29) and carcinoembryonic antigen (30)(31)(32). However, in middle-aged women with a breast finding suspicious for cancer, the test was insufficiently sensitive to allow a confident decision for or against biopsy, and falsepositive rates were too high for screening of low-risk populations.…”
Section: Discussionsupporting
confidence: 64%
“…To conclude, we found that AMAS testing discrimination of neoplasia was significantly different from random, with sensitivities and specificities similar to other clinical tests such as prostate-specific antigen (29) and carcinoembryonic antigen (30)(31)(32). However, in middle-aged women with a breast finding suspicious for cancer, the test was insufficiently sensitive to allow a confident decision for or against biopsy, and falsepositive rates were too high for screening of low-risk populations.…”
Section: Discussionsupporting
confidence: 64%
“…Elevated CA72-4 was associated with tumor depth [28,37,43], nodal involvement [10,12,20,24,28,34,37,42,43], peritoneal metastases [10,24,34,43], distant metastases [34,43], and stage [9,20,28,34,35,39,42,43]. Ucar et al [43] reported that 9 of 11 patients (82 %) with liver metastases were positive for CA72-4.…”
Section: Ca72-4mentioning
confidence: 99%
“…However, Guadagni et al 26 found no association between serosa involvement and elevated sera CA 19-9 levels. Early and advanced stages of GC confirmed after surgery based on positive or negative levels of CA 19.9 and their association with staging in Table V showed that when patients in stages early (I-II) and advanced (III-IV) were compared, significant difference was not observed for CA 19.9 (P=0.4).…”
Section: Discussionmentioning
confidence: 95%